(untitled) (Al-Academy, 2021)
The research deals with the formal characteristics of folklore in contemporary Iraqi ceramics as a comparative study between the two potters Siham Al-Saudi and Sajida Al-Mashayikhi.The research consists of four chapters. The first chapter is concerned with the research problem, the importance, the objectives, and the limits of the research, while the aim of the research answers the following question: The method and mechanisms of employing the traditional elements and vocabulary in the products of the potters “Seham Al-Saudi and Sajida Al-Mashaikhi”.The second chapter came in the theoretical framework of the investigations and includes: The first topic: The second topic the movement in shaping contemporary Iraqi ceramics, while the third chapter came in the investigation of research procedures and analysis of samples, while the fourth chapter came with the results of the research and comparison between the two potters and the most important results: The Saudi potter has invested in folkloric forms such as doors, arches and domes, as it is a guide to its religious and cultural reference. Folkloric formality. While the pottery works of "Sajida al-Mashaikhi" are evident in the faces that bear the imprint of the local identity of Baghdad, and within the formal metaphors of the local folk symbol by borrowing the feminine cloak. Finally, we conclude the search with the most important sources and references